Pengaruh Adversity Qoutient Terhadap Prestasi Akademik Santri Di Institut Agama Islam Tribakti Lirboyo Kediri - Muhammad Mahrus Amin; Miftahudin (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aimed to determine the effect of the Adversity Quotient on Academic Achievement of Students Domiciled in Pondok Pesantren Haji Ya'qub. The method used in this research is quantitative using a purposive sampling technique; the sample used is 69 respondents. The results show the Adversity Quotient's significant influence on students' academic achievement in Pondok Pesantren Haji Ya'qub.